Anaesthetic challenges in a patient with Klippel–Feil syndrome scheduled for panendoscopy and biopsy*. (4th March 2018) - Chitnis, A; Enohumah, KO
Abstract : Klippel–Feil syndrome is one of the congenital causes of difficult airway. It is characterised by a classic triad of a short neck, restricted cervical spine movement, and a low posterior hairline, which can pose a significant challenge to the anaesthetist during airway management. A case of Klippel Feil Syndrome type 2 with associated Sprengel's deformity for panendoscopy under general anaesthesia is presented. The anaesthetic considerations in the management of this patient are also discussed.